Growth of Cr-doped GaN Nanowires - Chen, Rongna; Gao, Faming; Gao, Xiaohong; Hou, Li (Asian Journal of Chemistry, 2013)
Cr-Doped GaN nanowires were fabricated using a chemical vapour deposition method. The structures, morphologies and compositions of the products have been characterized by powder X-ray diffraction, transmission electron microscopy, selected area electron diffraction and energy dispersive X-ray analysis. Results revealed that the obtained nanowires are single-crystal GaN with hexagonal wurtzite structure. TEM images show two different morphologies, the bent and the very straight nanostructures. The optical property of Cr-doped GaN was observed in the photoluminescence spectra, which shows the as-prepared product emits a strong UV light emission at 395 nm and a yellow luminescence at 580 nm (lex = 325 nm).